The Point of Intersection and Synergy of Islamic Economics and People's Economy - Dewi Kartika (Proceedings of AICS - Social Sciences, 2017)
In fact Islamic economics and people’s economy have the same purposes, economic welfare and justice for everyone. Based on Islam, justice and welfare in economics should be based on Islamic norms and ethics, so all of economic systems are running in accordance with Islamic Shari’s. People’s economy in Indonesia has been run for a long time by planned institution, which is cooperative. Cooperative is the spearhead which is expected by founding fathers of this state as a tool for economic equity and justice. In the concept and implementation, cooperative institution has much conformity with institutions of economic empowerment expected by Islam.